From CEDES to UCLA: Memories of Student and as Professor of Entomology (Revista Electrónica REDINE, 2018)
This paper presents a historic account of events experienced by students at the Universidad Centroccidental Lisandro Alvarado (UCLA) and the work done as a researcher and Entomology teacher (1965-2018). The document was prepared emphasizing in the first part, the high intellectual level of our teachers and experiences that took place in the teaching-learning process. Next, there is a description of the University Students’ March to Caracas, on November 1967, to demand the resignation of the authorities of the Centro Experimental de Estudios Superiores (CEDES) and the consolidation of the Universidad Experimental de la Región Centro Occidental (UERCO). In addition, this part of the document also refers to the founding of the Grape and Wine Institute by Dr. Luis A. Garassini and stresses the active participation of the students of the Agronomy School (1972-1974), led by Hugo Rivas Carnevali, President of the Student Union. The second part of the document makes reference to the activities performed in the classroom and in the laboratory, field trips for the day and night collection of insects used for research and teaching purposes, and for the development of the Museum of Entomology José Manuel Osorio (MJMO). Afterwards, a comment on a study carried out at University Park, The Pennsylvania State University, State College, Pennsylvania, USA (1976-1978) is made. The document ends up with reference to the work as professor of Entomology on the Obelisco Campus (1978-1990) and on the Dr. Hector Ochoa Zuleta Campus, at Tarabana, Cabudare (1990-2018), including teaching undergraduate students, and Agronomy and Veterinary graduate students in Master of Science Programs. Additionally, a list of the research work carried out during the professional life is shown, which gave rise to the presentation of papers at Entomology Congresses and to the publication of papers in national and international scientific journals.
Keywords: CEDES; department of entomology; student movement; UCLA; Venezuela